FORMULATION AND IN-VITRO EVALUATION OF LACIDIPINE ORAL DISINTEGRATING TABLETS: ENHANCEMENT OF SOLUBILITY AND DISSOLUTION RATE: Pharmaceutical Science-Pharmaceutics - KAMBHAM VENKATESWARLU; K.B.CHANDRASEKHAR (International Journal of Life Science and Pharma Research, 2022)
The aim of present study was to develop the Lacidipine oral disintegrating tablets (LCDP ODTs), thereby enhancing the solubility and dissolution rate. Solubility was enhanced by solid dispersion technology using hydrophilic carriers like Hydroxy Propyl Methyl Cellulose Acetate Succinate (HPMCAS), β-Cyclodextrin (BCD), Polyethylene Glycol 6000 (PEG 6000) and it was confirmed by phase solubility studies. LCDP ODTs were prepared by using super disintegrants like Croscarmellose Sodium (CCS), Crospovidone (CP), Sodium Starch glycolate (SSG). Evaluation parameters were complied with the official limits. From the in-vitro dissolution studies, it was observed that the formulation F9 consists of CP showed maximum drug release within short period of time.